Open for All: How Are Federal and Municipal Land Management Agencies Adapting to the COVID-19 Pandemic Alongside Increased Societal Recognition of Racial Injustice - Svendsen, Erika S.; Campbell, Lindsay K.; Plitt, Sophie; Johnson, Michelle L. (Frontiers in Sustainable Cities, 2021)
In addition to creating devastating impacts on human health and the economy, COVID-19 is changing the way humans interact with open space. Across urban to rural settings, many public lands--including forests, parks, and campgrounds--experienced increases and shifts in recreational use. Under anything but the most extreme lockdown, outdoor activities at safe distances were not only allowed, but encouraged for sustaining physical, mental, and emotional health and well-being. At the same time, with the occurrence of public uprisings around racial injustice throughout the country, public lands have become protest spaces. The COVID-19 crisis is revealing underlying inequities and vulnerabilities in U.S. society that cause people to experience risk and interact with the public realm in different ways. Land managers are having to adapt practices in real-time to our new and changing reality. In this study, we explore the role of the public land manager during this time across municipal and federal lands and an urban-rural gradient focusing on adaptations that occur across local conditions, leadership approaches, and varied relationship to external partnerships and networks. What are some of the place-based strategies and tactics used by land managers to adapt to the challenges of a pandemic while ensuring that the resource they steward remains accessible, safe, and welcoming for all people? How might these strategies and tactics inform future institutional change? This paper applies qualitative interview data drawn from a sample of managers across the northeastern United States to compare municipal and federal forest land management in terms of partnership arrangements, recreational and educational programs, and stakeholder engagement practices and to empirically examine Duchek’s model of organizational resilience. It finds that open and reflective communication and transboundary partners are critical assets during compound disturbances. The study highlights the importance of organizational culture and subcultures in shaping immediate and adaptive responses. By comparing different governing regimes and geographies, this paper intends to offer insight into how, why, and to what degree organizational resilience evolves within large bureaucratic institutions as they manage for public access, engagement, and recreation and refines Duchek’s model for public land manager and long-term disturbance contexts.